2003
DOI: 10.1055/s-2003-44597
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Ischaemia during Endoscopic Retrograde Cholangiopancreatography

Abstract: Myocardial ischaemia occurred in approximately one-quarter of patients during ERCP, and over half of these had no previous cardiac history and normal baseline electrocardiography results. Myocardial ischaemia often accompanied the use of sedation and intubation of the patient, but specific therapeutic interventions were not associated with the onset of ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…Mechanical effects of the use of a duodenoscope may also stimulate the sensorial afferents while it moves down the esophagus and may cause myocardial ischemia (22,23). Jonston showed that myocardial ischemia developed in approximately 25% of ERCP patients, half of whom had no previous cardiac history (15). Silent myocardial ischemia has been reported in the literature with different frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanical effects of the use of a duodenoscope may also stimulate the sensorial afferents while it moves down the esophagus and may cause myocardial ischemia (22,23). Jonston showed that myocardial ischemia developed in approximately 25% of ERCP patients, half of whom had no previous cardiac history (15). Silent myocardial ischemia has been reported in the literature with different frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Silent myocardial ischemia has been reported in the literature with different frequencies. Vieire found a 2% frequency in 50 patients (13); Lee detected a 18.3% frequency; among 71 patients, one of whom had a myocardial infarction (14), Johnston detected 22% in 41 patients (15); and Fisher reported 8%, of whom 2 died (16). Changes of ST wave in the ECG may not be related with a pre-existing cardiac problem (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study with 41 patients undergoing ERCP under conscious sedation, Johnston et al [37] revealed that one quar ter of patients had myocardial ischemia and over half of them had no previous cardiac history and normal baseline electrocardiography results.…”
Section: Assessing Sedation-related Complicationsmentioning
confidence: 99%